Shaping the Religious Character of Students from Fishermen Families Through Islamic Religious Education and Character Building - Yayat Hidayat; Mahmud Manan; Muslihun Muslihun (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2025)
This research examines how Islamic education shapes the religious character of students from fishing families at SMAN 1 Parigi Pangandaran through intracurricular and extracurricular learning, along with the supporting and inhibiting factors involved. Using a qualitative case study approach, data were collected through observations, interviews, and documentation. Data analysis involved reduction, presentation, and conclusion drawing, with validity ensured through triangulation. The study found that Islamic education is implemented in two key ways: 1) Intracurricular learning, which enhances religious understanding, emotional stability, and student engagement, fostering greater trust and interactive learning; 2) Extracurricular learning, which strengthens religious character, discipline, responsibility, and integrity, while promoting harmony within the school environment. Supporting factors include student motivation, the availability of BPI books, and complete facilities. Inhibiting factors include external negative influences, student fatigue, and low awareness of the importance of religious values. The implementation of Islamic education at SMAN 1 Parigi Pangandaran has significant implications for shaping students' religious character academically and socially. This research contributes to the broader development of Islamic education in Indonesia.